Obtaining nanosized niobium and tantalum pentoxides by using supercritical antisolvent fluid technology - K. A. Smirnova; V. V. Fomichev; D. V. Drobot; E. E. Nikishina (Тонкие химические технологии)
Niobium and tantalum methylates with common formula M2(OMe)10 , where M - Nb,Ta, have been synthesized as precursors by electrochemical synthesis for obtaining niobium and tantalum oxides. Ultradispersed and nanosized oxides TT (δ)-Nb2O5 and T (γ)-Ta2O5 were obtained by supercritical fluid technology. The samples are characterized by different methods (chemical analysis, DTA-DTG, XRD, IR-spectroscopy, grain size analysis). It is shown that under the experimental conditions amorphous particles of niobium and tantalum pentoxides are formed, which react to form the crystalline state at temperatures of 600°C and 750°C respectively. Crystallization temperature of T(γ)-Ta2O5 obtained by SAS-technology significantly lower than the crystallization temperature of the same tantalum pentoxide obtained by heterophasic method (900°C). The particle size of the annealed tantalum pentoxide is in the range of nanosized materials, particle size of the annealed niobium pentoxide qualifies them as ultradispersed.